Energy Analysis of Diesel Engine With B30 at PLTD Selat Panjang - Romy Romy; Bagus Trianto (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2022)
Many efforts have been made in energy efficiency in power plants. One way to improve the efficiency of energy use is to conduct analysis. The purpose of this study was to analyze the thermal efficiency of a diesel engine with B30 at PLTD Selat Panjang unit 4. The data were collected using a daily operation report log sheet for Caterpillar 3512B diesel with duration 3x24. From the calculation carried out, the average thermal efficiency of diesel engine with B30 as fuel at PLTD Selat Panjang was 47.52%.